Occurrence of veterinary antibiotics and progesterone in broiler manure and agricultural soil in Malaysia - Ho, Yu Bin; Zakaria, Mohamad Pauzi; Abdul Latif, Puziah; Saari, Nazamid (Elsevier, 2014)
Repeated applications of animal manure as fertilizer are normal agricultural practices that may release veterinary antibiotics and hormones into the environment from treated animals. Broiler manure samples and their respective manure-amended agricultural soil samples were collected in selected locations in the states of Selangor, Negeri Sembilan and Melaka in Malaysia to identify and quantify veterinary antibiotic and hormone residues in the environment. The samples were analyzed using ultrasonic extraction followed by solid phase extraction (SPE) and liquid chromatography–tandem mass spectrometry (LC–MS/MS). The broiler manure samples were found to be contaminated with at least six target analytes, namely, doxycycline, enrofloxacin, flumequine, norfloxacin, trimethoprim and tylosin. These analytes were detected in broiler manure samples with maximum concentrations reaching up to 78,516 μg kg− 1 dry weight (DW) (doxycycline). For manure-amended agricultural soil samples, doxycycline and enrofloxacin residues were detected in every soil sample. The maximum concentration of antibiotic detected in soil was 1331 μg kg− 1 DW (flumequine). The occurrence of antibiotics and hormones in animal manure at high concentration poses a risk of contaminating agricultural soil via fertilization with animal manure. Some physico-chemical parameters such as pH, total organic carbon (TOC) and metal content played a considerable role in the fate of the target veterinary antibiotics and progesterone in the environment. It was suggested that these parameters can affect the adsorption of pharmaceuticals to solid environmental matrices.